Applications of Wi-Fi based robots - S. , Rohith; R. , Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we have been described about WI-FI-based robots, as the technology is increasing day by day, robot usage has been increasing more, and safety is another issue while making these robots. AI and industrial technology are main terms to develop the robots. There are different kinds of wifi-controlled robots pipeline robot, wheeled robot, autonomous robots these are mobile robots. robot vision helps the robot to navigate itself or either we can give intimations to that robot. For operation of robot, we can use Aurdino, Rotatory ultrasonic sensor. Buzzers and LEDs will help if any obstacle has come .There are some speech recognition robots that work under robot operating system. with the navigation system, we can move the robots through the computers. This robotic platform supports innovation in advanced technology. These robots have the capability to find its own position and the other positions through some aurdino. Due to the extensive development and improved intelligent fingerprint positioning technology of robots.